2001
DOI: 10.1128/mcb.21.16.5500-5511.2001
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Protein Translation by Mitogen-Activated Protein Kinase-Interacting Kinases 1 and 2

Abstract: Eukaryotic initiation factor 4E (eIF4E) is a key component of the translational machinery and an important modulator of cell growth and proliferation. The activity of eIF4E is thought to be regulated by interaction with inhibitory binding proteins (4E-BPs) and phosphorylation by mitogen-activated protein (MAP) kinase-interacting kinase (MNK) on Ser209 in response to mitogens and cellular stress. Here we demonstrate that phosphorylation of eIF4E via MNK1 is mediated via the activation of either the Erk or p38 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
190
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(209 citation statements)
references
References 40 publications
18
190
1
Order By: Relevance
“…Many of the studies cited in this review used the Mnk inhibitor CGP57380 which targets both Mnk1 and Mnk2. CGP57380 is a low weight molecular compound that was identified from the Novartis Pharma compound collection by in vitro kinase assays [127] and the IC50 against Mnk1 is seen at a concentration of 2.2 μM [9]. Additionally CGP57380 inhibits casein kinase, MAP2K1 and BR serine/threonine-protein kinase 2 at concentrations comparable to those required for Mnk inhibition [128].…”
Section: Rantesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies cited in this review used the Mnk inhibitor CGP57380 which targets both Mnk1 and Mnk2. CGP57380 is a low weight molecular compound that was identified from the Novartis Pharma compound collection by in vitro kinase assays [127] and the IC50 against Mnk1 is seen at a concentration of 2.2 μM [9]. Additionally CGP57380 inhibits casein kinase, MAP2K1 and BR serine/threonine-protein kinase 2 at concentrations comparable to those required for Mnk inhibition [128].…”
Section: Rantesmentioning
confidence: 99%
“…Moreover, Mnk1/2 −/− mice do not have impaired rate of protein synthesis or cap dependent translation [8]. In another study, the expression of constitutively active Mnk1 and Mnk2 mutants or the activation of Mnk1 by stimulation of either p38 or Erk was found to diminish the rate of cap dependent translation relative to the internal ribosome entry site (IRES) mediated translation [9]. Given the reduced affinity of capped RNA for phosphorylated eIF4E it has been suggested that phosphorylation on S209 may result in the disassociation of eIF4E from the initiation complex allowing the 40S ribosome to scan for the initiation codon [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2d depicts a Western blot of MNK1 overexpression in the MNK1 stable cell line compared to cells containing pcDNA3 as the empty control vector. To gain insight into a potential role of MNK1 in eIF4E phosphorylation, we employed a potent small molecular weight inhibitor (CGP57380), which was a kind gift of Dr Gram (Novartis, Knauf et al, 2001). Experiments performed in the presence and absence of the MNK1 inhibitor CGP57380 showed that the eIF4E translation factor was consistently detectable and its expression levels were not altered by MNK1 overexpression.…”
Section: Induction Of Mnk1 Protein By Aml Fusion Proteins and Its Expmentioning
confidence: 99%
“…Empty vector (pcDNA3)-transfected 32D cells served as control. MNK1-MA is a kinasedeficient mutant and MNK1-AA contains a mutation at a phosphorylation site (Knauf et al, 2001). Both MNK1 mutants are inactive in MNK1 function and could potentially function as dominant negative proteins.…”
Section: D Cell Proliferation Depends On Mnk1 Functionmentioning
confidence: 99%
See 1 more Smart Citation